Detection of HPV16 in esophageal cancer in a high-incidence region of Malawi - Geßner, Anja Lidwina; Wilhelm, Torsten (International journal of molecular sciences, 2018)
This study was designed to explore the role of human papillomavirus (HPV) in esophageal squamous cell carcinoma (ESCC). Fifty-five patients receiving diagnostic upper gastrointestinal endoscopy at Zomba Central Hospital or Queen Elizabeth Hospital in Blantyre (Malawi) in 2010, were included in our study. Formalin-fixed paraffin-embedded biopsies were collected for histopathological diagnosis. HPV DNA was detected using multiplex Quantitative PCR (qPCR) and in situ hybridization (ISH). p16INK4a staining served as a surrogate marker for HPV oncogene activity. Cell proliferation was determined by Ki-67 staining. Human immunodeficiency virus (HIV) status was evaluated by serology. Data on the consumption of alcohol and tobacco, and history of tuberculosis (TBC), oral thrush, and Herpes zoster, were obtained by questionnaire. Forty patients displayed ESCC, three displayed dysplastic epithelium, and 12 displayed normal epithelium. HPV16 was detected in six ESCC specimens and in one dysplastic lesion. Among HPV-positive patients, viral load varied from 0.001 to 2.5 copies per tumor cell. HPV DNA presence could not be confirmed by ISH. p16INK4a positivity correlated with the presence of HPV DNA (p = 0.03). Of particular note is that the Ki-67 proliferation index, in areas with diffuse nuclear or cytoplasmatic p16INK4a staining ≥50%, was significantly higher in HPV-positive tumors compared to the corresponding p16INK4a stained areas of HPV-negative tumors (p = 0.004). HPV infection in ESCC was not associated with the consumption of tobacco or alcohol, but there were significantly more patients drinking locally brewed alcohol among HPV-positive tumor patients compared to non-tumor patients (p = 0.02) and compared to HPV-negative tumor patients (p = 0.047). There was no association between HIV infection, history of TBC, Herpes zoster, oral thrush, or HPV infection, in ESCC patients. Our indirect evidence for viral oncogene activity is restricted to single tumor cell areas, indicative of the role of HPV16 in the development of ESCC. The inhomogeneous presence of the virus within the tumor is reminiscent of the “hit and run” mechanism discussed for β-HPV types, such as HPV38.
Gesehen am 01.04.2019